Kajian Tingkat Pemahaman dan Persepsi Masyarakat Tentang Wakaf Uang sebagai Solusi dalam Pengentasan Kemiskinan di Kota Bengkulu - Hamilatul Hasanah Putri; Ratu Eva Febriani (Universitas Bengkulu, 2021)
This research is a qualitative research which aims to determine the level of understanding and views of the people of Bengkulu City about cash waqf as a solution to poverty alleviation in Bengkulu City. The data used are primary data obtained through questionnaires distributed directly or indirectly (questionnaires online). The results showed that the level of understanding of the people of Bengkulu City about cash waqf was still low and the public view of cash waqf as a solution to poverty alleviation in Bengkulu City was good, where the average Bengkulu City community thought that cash waqf if applied in Bengkulu City would have a positive impact. for the economy in Bengkulu City.